Edible gelatin/glycerol coating added with rosemary essential oil (Rosmarinus officinalis L.) increases pork loin shelf life - Guimarães, Isabela Costa; Marques, David Roger Paixão; Miranda, Ana Luiza de Souza; Cardoso, Giselle Pereira (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
The use of plastic as packaging for food preservation has been questioned due to its great environmental impact. Thus, we seek new alternatives to reduce the non-biodegradable material use and add value to packaged food. The edible coating use is a very viable alternative, not only because it reduces the use of plastic, but also because it acts as an active packaging. Elements that improve its properties, such as the addition of essential oil, can be added to it. This work aims to evaluate the effect of gelatin-based coating with rosemary essential oil addition during 8 days of cold storage of pork loin. The coated samples added with rosemary essential oil obtained better responses to the pH, weight loss, firmness, lipid oxidation, and microbiological growth analyzes, proving to be a great alternative for refrigerated meat conservation. In sensory evaluation, no significant difference was observed between the control and the coated meat.